EXTENT OF HEMODIALYSIS NURSES’ PRESENCE AS PERCEIVED BY PATIENTS - Ma. Almira Pliego Nebres; Clarence Bien Ladion Nebres; Bienvisa Ladion Nebres (Belitung Nursing Journal, 2020)
Background: Nursing presence is an essential nurse caring behavior of being with the patient. This is particularly true for those with chronic renal disease and who regularly undergo maintenance hemodialysis treatment in the hospital setting. When nursing presence is perceived by patients in a nurse-patient relationship, it is more likely to result in enhanced satisfaction with the quality of nursing care. Thus, it is important for hemodialysis nurses to be aware of the relevance of nurse-patient interactions in planned care considering that these interactions are integral to the extent to which nursing presence is experienced and perceived by patients.Objective: This study aims to determine the hemodialysis nurses’ extent of nursing presence as perceived by patients undergoing hemodialysis treatment in two hospitals in Iligan City, Philippines.Methods: Utilizing the descriptive research design, the study was conducted in two hospitals in Iligan City, Philippines.  A total of 121 hemodialysis patients were purposely selected to determine their perception as to the extent of hemodialysis nurse’s nursing presence utilizing the 25-item Presence of Nursing Scale (PONS) instrument. Descriptive statistics were used for data analysis.Result: The overall rating by the hemodialysis patients in both hospitals was “always" on the hemodialysis nurses’ extent of nursing presence with an average mean score of 4.47 in all 25 items of the PONS. The highest rated item which reflects that the nurse cares for the patient as a person had an average mean score of 4.63 (always) while the lowest rated item indicating that the nurse is meeting the spiritual needs of the patient had an average mean score of 4.23 (always).Conclusion: The nurse-patient relationship is enhanced by the presence of nurses who are more responsive and interactive with the patients, resulting in patients who are more satisfied with nursing care. Thus, it is suggested that nurses in dealing with patients of varying backgrounds should consider their unique needs when giving information, explanations, health education and nursing care.